Emotionally focused couple therapy in cancer survivor couples with marital and sexual problems: a replicated single-case experimental design - van Diest, Selma L.; den Oudsten, Brenda L.; Aaronson, Neil K.; Beaulen, Audrey; Verboon, Peter; Aarnoudse, Berry; van Lankveld, Jacques J. D. M. (Frontiers in Psychology, 2023)
The current research examined the effect of Emotionally Focused Couples Therapy (EFCT) on perceived intimacy, affect, and dyadic connection in cancer survivor couples with relationship challenges. In this longitudinal replicated single-case study, positive and negative affect, intimacy, partner responsiveness, and expression of attachment-based emotional needs were reported every three days before and during treatment. Thirteen couples, with one partner having survived colorectal cancer or breast cancer, participated for the full duration of the study. Statistical analysis of the data was performed using randomisation tests, piecewise regression, and multilevel analyses. Adherence to the therapeutic protocol was tested and found adequate. Compared with baseline, significant positive effects on affect variables were found during the therapeutic process. Positive affect increased and negative affect decreased. Partner responsiveness, perceived intimacy, and the expression of attachment-based emotional needs improved, but only in the later phase of treatment. Results at the group level were statistically significant, whereas effects at the individual level were not. This study found positive group-level effects of EFCT on affect and dyadic outcome measures in cancer survivors. The positive results warrant further research, including randomised clinical trials, to replicate these effects of EFCT in cancer survivor couples experiencing marital and sexual problems.